MENINGKATKAN KEMAMPUAN SERVICE DALAM PERMAINAN BOLA VOLLY DENGAN MAKE A MATCH PADA SISWA KELAS VII-H SMP NEGERI 1 WONOASRI - Anik Sri Handayani (Universitas PGRI Madiun, 2014)
In the learning process of Physical Education in, teachers are expected to teach varieties of basic motor skills, techniques and strategy of games and sports, internalization of values (sportsmanship, honesty, cooperation, etc.) as well as the conditioning of healthy lifestyles. The implementation is not through conventional teaching in the classroom consisting theoretical studies, but it also involves elements of physical, mental, intellectual, emotional and social. The activities which are given in teaching should get a methodical didactic touch, so that the activities carried out can achieve the aim of teaching. The problem formulation of this research is: is there an increase in the ability of service in the game of volleyball with “make-match” at VII-H grade of SMP Negeri 1 Wonoasri in 2012/2013 academic year? The purpose Classroom Action Research (CAR) is to improve the quality of learning on the physical education in doing “service” in a volleyball game through a “make-match” learning approach In this study, researchers have collaboration with other teachers and the principal. Researchers are involved in the study from the beginning to the end of the researech. Researchers try to see, observe, feel, live, reflect and evaluate learning activities that take place. The implementation stages of the action research consist of planning, acting, observation, and reflection. To obtain accurate results, the collected data in study were statistically analyzed using the formulas of mean or average. The result showed that the average value of the first cycle of 66.14 (46.33%) while the Cycle II 91.29 (96.43%) in the second cycle, it has increased significantly. Referring to the hypothesis that the actions proposed in this class action research, it can be concluded that: there is an increased ability of “service” in volleyball games with “make-a-match” at VII-H grade of SMP Negeri 1 Wonoasri in 2012/2013 academic year. Keywords: Skill Upgrading, Make A-Match